Impact of National Debt Burden on Economic Stability in Nigeria - Onyele Kingsley Onyekachi; Nwadike Emmanuel Chijioke (Economics and Business)
The study argues that national debt becomes a burden when debt overhang is rising, a foreign reserve is inadequate to cover short-term external debt and government revenue is inadequate for debt servicing. This paper investigates the impact of national debt burden on economic stability in Nigeria. Data spanning from 1981 to 2019 have been collated from the World Development Indicators and Central Bank of Nigeria Statistical Bulletin, 2019 edition. Consequently, the variables used to measure debt burden are total debt-to-GDP ratio (debt overhang), short-term external debt-to-reserves ratio (reserve adequacy) and debt service cost-to-government revenue ratio (revenue adequacy) with exchange rate as a control variable, while economic stability is measured with real GDP growth rate. The Autoregressive Distributed Lag (ARDL) model is used for the analysis since the variables are stationary at both levels and first difference. The ARDL estimation shows that the explanatory variables collectively cause a diminishing impact on economic stability in the long run with revenue adequacy having a negative and significant impact. In the short run, all the components of debt burden, except debt overhang, have a negative and significant impact on economic stability. Under this circumstance, exchange rate has a positive and significant impact on economic stability in the long run.